Envisioning 5G-Enabled Transport - Monserrat, Jose F.; Diehl, Adam; Bellas Lamas, Carlos; Sultan, Sara (World Bank, Washington, DC, 2021)
The transport industry has entered a period of rapid advancement, and the pace of change is only increasing. The proliferation of electric vehicles, rapid advances in autonomous vehicles, the advent of the sharing economy and digital platforms, advances in big data and machine learning, and rapidly evolving business models, such as eCommerce and Mobility as a Service (MaaS), are causing profound changes throughout the sector. The development and rollout of fifth-generation (5G) mobile broadband has the potential to not only support, but accelerate these revolutionary changes as today’s digital transport solutions evolve and entirely new opportunities become viable. 5G presents a variety of benefits over previous generations of wireless connectivity, including greater bandwidth, lower latency, capacity to dedicate resources for critical functions, potential for greatly expanded numbers of devices, and easy sharing of data. In some cases, we see dramatic and exponential gains from previous technologies. Each of these 5G features will have an impact in the transport sector, contributing to transport-specific applications. Of these, three key opportunities present themselves: (1) revolutionary advancements in the potential connectivity of vehicles, (2) an increase in the number and ubiquity of connected devices, and (3) improved data availability for transport operations and management. When applying these new technologies to transport, changes can be expected across the sector, with—to some extent—no corner left untouched. While impossible to foresee all potential applications, the study predicts three likely and significant changes: (1) the rise of connected and autonomous vehicles, (2) increasingly smart and efficient logistics, and (3) improved urban transportation with the implementation of MaaS platforms. Figure E.1 highlights some of these key impact linkages between 5G and the transport sector. 5G-enabled vehicles will differ from those in use today, with business models in the transport sector expected to differ significantly from the current paradigm. Connected and autonomous vehicles (CAVs) will bring together a series of changes impacting the sector, including connectivity, electrification, autonomy, and new business models such as MaaS. While the connectivity provided by 5G represents only one enabling facet of this equation, it fundamentally changes the overall potential scope and viability of the model.